2011
DOI: 10.1136/hrt.2010.216499
|View full text |Cite
|
Sign up to set email alerts
|

Cilostazol attenuates on-treatment platelet reactivity in patients with CYP2C19 loss of function alleles receiving dual antiplatelet therapy: a genetic substudy of the CILON-T randomised controlled trial

Abstract: TAT significantly reduced OPR compared with DAT in carriers of the CYP2C19 LOF allele, but not in non-carriers. These data suggest that the addition of cilostazol to DAT may be a good strategy to attenuate CYP2C19 LOF-related high OPR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 35 publications
3
27
0
2
Order By: Relevance
“…However, a study from the Netherlands of 1069 clopidogrel-pretreated patients undergoing elective PCI found that loss-offunction CYP2C19 carrier status explained only part of the variability in platelet reactivity (13.0-20.6%), depending on the test used (37). One approach to modifying high on-treatment platelet reactivity in carriers of loss-of-function CYP2C19 variants is to use antiplatelet drugs metabolised by different pathways, and this was confirmed by investigators from Korea in a substudy of the CILON-T randomised trial (38). In patients with loss-offunction CYP2C19 variants who were randomised to dual antiplatelet therapy plus cilostazol, a selective phosphodiesterase-3 inhibitor, on-treatment platelet reactivity was significantly reduced compared with patients who received only aspirin and clopidogrel.…”
Section: Optimal Arterial Accessmentioning
confidence: 67%
“…However, a study from the Netherlands of 1069 clopidogrel-pretreated patients undergoing elective PCI found that loss-offunction CYP2C19 carrier status explained only part of the variability in platelet reactivity (13.0-20.6%), depending on the test used (37). One approach to modifying high on-treatment platelet reactivity in carriers of loss-of-function CYP2C19 variants is to use antiplatelet drugs metabolised by different pathways, and this was confirmed by investigators from Korea in a substudy of the CILON-T randomised trial (38). In patients with loss-offunction CYP2C19 variants who were randomised to dual antiplatelet therapy plus cilostazol, a selective phosphodiesterase-3 inhibitor, on-treatment platelet reactivity was significantly reduced compared with patients who received only aspirin and clopidogrel.…”
Section: Optimal Arterial Accessmentioning
confidence: 67%
“…37 One approach to modifying high on-treatment platelet reactivity in carriers of loss-of-function CYP2C19 variants is to use antiplatelet drugs metabolised by different pathways, and this was confirmed by investigators from Korea in a substudy of the CILON-T randomised trial. 38 In patients with loss-of-function CYP2C19 variants who were randomised to dual antiplatelet therapy plus cilostazol, a selective phosphodiesterase-3 inhibitor, on-treatment platelet reactivity was significantly reduced compared with patients who received only aspirin and clopidogrel. This effect of cilostazol was not seen in non-carriers of the loss-offunction polymorphism.…”
Section: Antiplatelet Therapiesdwhat's New?mentioning
confidence: 99%
“…37 One approach to modifying high on-treatment platelet reactivity in carriers of loss-of-function CYP2C19 variants is to use antiplatelet drugs metabolised by different pathways, and this was confirmed by investigators from Korea in a substudy of the CILON-T randomised trial. 38 In patients with loss-of-function CYP2C19 vari ants who were randomised to dual antiplatelet therapy plus cilostazol, a selective phosphodiesterase-3 inhibitor, on-treatment platelet reactivity was significantly reduced compared with patients who received only aspirin and clopidogrel. This effect of cilostazol was not seen in non-carriers of the loss-of-function polymorphism.…”
Section: Antiplatelet Therapies-what's New?mentioning
confidence: 99%